Technical and clinical success analysis of transarterial embolization therapy in type II endoleaks following endovascular aortic repair - Krompaß, Kristina; Grunz, Jan-Peter; Augustin, Anne Marie; Peter, Dominik; Schönleben, Frank; Bley, Thorsten; Kickuth, Ralph (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2024)
This single-center study investigated the safety and efficacy of transarterial embolization of type II endoleaks for expanding aneurysm sacs following endovascular aortic repair (EVAR).36 patients (33 men, 75.9±6.6 years) underwent a total of 50 endovascular procedures for type II endoleak embolization between 2008 and 2023. Analyses included the assessment of patient risk profiles, aneurysm morphology, and endoleak characteristics. Outcome parameters comprised the technical success (i.e., complete lack of blood flow in the previously perfused aneurysm sac) and complication rates, while clinical success was defined as the absence of endoleak persistence or recurrence and freedom from aneurysm enlargement > 0.5 cm over the follow-up period.Transarterial embolization was technically successful in 84% of procedures with a complication rate of 2%. Most interventions were coil-based (72%), while a small number relied solely on liquid embolic agents (14%). Absence of a persisting endoleak in the earliest follow-up could be demonstrated in 75.6% of cases, whereas the absence rate for endoleak recurrence was substantially lower (46.3%). No aneurysm enlargement > 0.5 cm during follow-up was ascertained after 73.2% of interventions.Transarterial embolization represents a safe treatment for type II endoleaks after EVAR. While embolization was moderately effective in preventing further expansion of aneurysms due to endoleak recurrence, most procedures were successful in permanently eliminating the targeted feeder vessels.
Keywords: Type II endoleak; Digital subtraction angiography; Transarterial embolization; Procedural success; Outcome analysis